A Novel Approach to the Measurement of Bourdieusian Social Capital within Institutional Pages and Profiles - Gomes, Alan Keller; Cunha, Kaique Matheus Rodrigues; Ferreira, Guilherme Augusto da Silva (Revista de Informática Teórica e Aplicada, 2022)
We present in this paper a novel approach for measuring Bourdieusian Social Capital (BSC) within Institutional Pages and Profiles. We analyse Facebook’s Institutional Pages and Twitter’s Institutional Profiles. Supported by Pierre Bourdie’s theory, we search for directions to identify and capture data related to sociability practices, i. e. actions performed such as Like, Comment and Share. The system of symbolic exchanges and mutual recognition treated by Pierre Bourdieu is represented and extracted automatically from these data in the form of generalized sequential patterns. In this format, the social interactions captured from each page are represented as sequences of actions. Next, we also use such data to measure the frequency of occurrence of each sequence. From such frequencies, we compute the effective mobilization capacity. Finally, the volume of BSC is computed based on the capacity of effective mobilization, the number of social interactions captured and the number of followers on each page. The results are aligned with Bourdieu’s theory. The approach can be generalized to institutional pages or profiles in Online Social Networks.